2011
DOI: 10.1093/jpepsy/jsq117
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Related Health Behaviors Among Urban and Rural Children in the United States: Data from the National Health and Nutrition Examination Survey 2003-2004 and 2005-2006

Abstract: There are modifiable health behavior differences between rural and urban children which may account for the significantly higher obesity rates among rural children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
3
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(165 citation statements)
references
References 23 publications
7
150
3
5
Order By: Relevance
“…This prevalence of childhood obesity within our sample is significantly greater than the national average of 17% as defined by the CDC (2). Although various studies have identified higher obesity rates in children living in rural areas than non-rural areas (4,20), other evidence supports our findings demonstrating higher than average levels of obesity in urban youth populations (8,21). Findings from this study reinforce the concern that childhood obesity is a major health issue, especially in urban youth populations that frequently lack resources, green spaces, adult supports, and consistent access to opportunities for physical activity, and reinforce the national concern about childhood obesity and its health threat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevalence of childhood obesity within our sample is significantly greater than the national average of 17% as defined by the CDC (2). Although various studies have identified higher obesity rates in children living in rural areas than non-rural areas (4,20), other evidence supports our findings demonstrating higher than average levels of obesity in urban youth populations (8,21). Findings from this study reinforce the concern that childhood obesity is a major health issue, especially in urban youth populations that frequently lack resources, green spaces, adult supports, and consistent access to opportunities for physical activity, and reinforce the national concern about childhood obesity and its health threat.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity rates tend to be highest among children in families who function at or below the poverty threshold (2). While studies have found higher than average prevalence of obesity in urban youth (3), comparative studies indicate that children residing in rural areas also run higher than average risk of obesity (4,5) with children in rural areas having up to 30% greater chance of being overweight or obese than children in non-rural areas even after adjustments for sociodemographic, health, diet and exercise (6).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggest that merely living in a certain geographic location is not, in itself, a risk factor, but factors that differ between urban/rural residence contribute to the observed differences in CVD risk factors 14 . Others argue that there remains a strong link between rurality and obesity that cannot be explained by demographic factors alone 15 …”
mentioning
confidence: 99%
“…Recent studies measuring intake of fruits, vegetables, and sugar sweetened beverages reveal adolescents are not meeting nutritional guidelines (Davis, Bennett, Befort, & Nollen, 2011;Eaton et al, 2012). In 2011, only 20.9% of adolescents nationwide reported not drinking any cans of soda pop in the last week, with 11.3% of adolescents drinking three or more cans of soda pop daily.…”
Section: Consideration Of Lifestyle Behaviors Among Adolescents Is Immentioning
confidence: 99%
“…In addition, 4.8% of adolescents nationwide had not eaten any fruit within the last 7 days, while 5.7% of adolescents had not eaten any vegetables within the last week (Eaton et al, 2012). Nutrition indicators suggest adolescents living in rural and urban areas have similar nutrition status (Davis et al, 2011).…”
Section: Consideration Of Lifestyle Behaviors Among Adolescents Is Immentioning
confidence: 99%